PENGARUH KOMPETENSI, INDEPENDENSI, DAN PROFESIONALISME AUDITOR INTERNAL DALAM MENCEGAH KECURANGAN PADA BPR DI KABUPATEN BADUNG - Windasari, Made Yunita; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
This research aimed to determine the effect of competence, independence and professionalism of internal auditors in preventing fraud. The theory used in this research is Theory Of Reasoned Actio and Theory Of Planned Behavior. The population in this study is the internal auditor BPR. This study uses non-probability sampling with saturated sampling. These samples were taken from all members of the population that is as much as 52 BPR. The Collected data using by questionnaires. The data analysis technique used in this research is multiple linear regression. The results of this research showed that the competence of the internal auditor, internal auditor independence and professionalism of the internal auditor of the positive effect on fraud in the BPR in Badung.
Keywords: competence; independence; professionalism; cheating internal auditor